Ammonothermal Synthesis, X‐Ray and Time‐of‐Flight Neutron Crystal‐Structure Determination, and Vibrational Properties of Barium Guanidinate, Ba(CN3H4)2. Issue 3 (14th March 2019) - Benz, Sebastian; Missong, Ronja; Ogutu, George; Stoffel, Ralf P.; Englert, Ulli; Torii, Shuki; Miao, Ping; Kamiyama, Takashi; Dronskowski, Richard
Abstract: We report the crystal structure of Ba(CN3 H4 )2 as synthesized from liquid ammonia. Structure solution based on X‐ray diffraction data suffers from a severe pseudo‐tetragonal problem due to extreme scattering contrast, so the true monoclinic symmetry is detectable only from neutron powder diffraction patterns, and structure solution and refinement was greatly aided by density‐functional theory. The symmetry lowering is due to slight deviations of the guanidinate anion from the mirror plane in space group P 4 ‾ b 2, a necessity of hydrogen bonding. At 300 K, barium guanidinate crystallizes in P 21 / c with a =6.26439(2) Å, b =16.58527(5) Å, c =6.25960(2) Å, and a monoclinic angle of β=90.000(1)°. To improve the data‐to‐parameter ratio, anisotropic displacement parameters from first‐principles theory were incorporated in the neutron refinement. Given the correct structural model, the positional parameters of the heavy atoms were also refinable from X‐ray diffraction of a twinned crystal. The two independent guanidinate anions adopt the all‐ trans ‐ and the anti ‐shape. The Ba cation is coordinated by eight imino nitrogens in a square antiprism with Ba−N contacts between 2.81 and 3.04 Å. The IR and Raman spectra of barium guanidinate were compared with DFT‐calculated phonon spectra to identify the vibrational modes. Abstract : All about that Ba : We report the oxidation‐controlled synthesis of barium guanidinate Ba(CN3 H4 )2 from liquid ammonia and discuss the crystal‐structure determination of the severely pseudo‐symmetrical monoclinic phase from high‐resolution neutron powder diffraction aided by first‐principles electronic‐structure theory. The infrared and Raman spectra have been assigned from first‐principles phonon calculations.